Application of Arabic Language Learning through Singing Methods to Improve Arabic Vocabulary in Children 5-6 Years Old - Firdausi, Lailatul; Buchari, Imam; Muiz, Abdul (Universitas Al-Amien Prenduan, 2025)
This study aims to describe the implementation of singing methods in improving Arabic vocabulary mastery in early childhood at Kartini Kindergarten. This research was chosen based on observations of the use of singing methods often implemented in 5-6 years old students in group B. However, there was no habit of using Arabic songs in singing, so the researcher took the initiative to implement singing methods associated with the use of vocabulary in order to improve the Arabic vocabulary of 5-6 years old children in group B at Kartini Kindergarten. The approach used in this study was descriptive qualitative with data collection techniques through observation and interviews with teachers. Data analysis was carried out through reduction, presentation, and inductive conclusion drawing. The results of the study show that the application of a structured singing method is effective in enriching children's Arabic vocabulary. The songs used are adapted to the learning theme and supported by song movements, thereby increasing creativity and confidence in students. It can be concluded that in this study, the singing method suggests that it is an effective and relevant strategy for increasing Arabic vocabulary in children aged 5–6 years.